Implementation of Group Guidance Model to Improve Students’ Responsibilities in Learning Activities in Class XI IPS2 - Sri Wahyuni (STKIP Singkawang, 2020)
This study aims to improve the students' responsibilities in following learning activities in class XI IPS2 by implementing the group guidance model. The population in this study were all students of class XI IPS2 SMA Negeri 1 Wirosari Academic Year 2018/2019. The sample was 12 students who have a problem with low student responsibility in following learning activities in class XI IPS2. The data collection method in this study used the observation method to reveal data about increasing students' responsibilities during group guidance activities and students' learning activities. The data analysis used descriptive analysis. The results showed that the students' responsibilities in following learning activities in class XI IPS2 by implementing the group guidance model increased very significantly. This could be shown from the result of the initial condition of the students' responsibilities in following learning activities class XI IPS2 by 0%. In cycle one there was an increase in students' responsibilities by 46%.